Penerapan Arsitektur Tropis pada Bangunan Shopping Center di Kota Lubuk Pakam, Kabupaten Deli Serdang - Siregar, Abdurrahman; Budiani, Ina Triesna (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
Shopping centers are centers of exchange and distribution of goods and services that play an important role in the economic development of a region. This author highlights the role and impact of modern shopping center development on urban development, with a focus on the city of Lubuk Pakam, Deli Serdang Regency, North Sumatra. Currently, the city has only one shopping center, Delimas Plaza, which is inadequate to meet the needs of the local community. By considering these conditions, this author proposes the construction of a Shopping Center in Lubuk Pakam by applying a tropical architecture theme. This theme was chosen because it can accommodate the tropical climate and weather in Indonesia. The design of the Shopping Center building is designed with attention to natural lighting and optimal air output. The development of Shopping Center in Lubuk Pakam is expected to have a positive impact on the development of the local economy, such as employment and increased tax revenue. In addition, with a more modern and complete shopping center, it is expected that the local community will no longer need to go to downtown Medan to shop, thus enabling better local economic development and growth.